1996
DOI: 10.1038/bjc.1996.520
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of radiotherapy response of cervical carcinoma through measurement of proliferation rate

Abstract: Summary Estimation of tumour proliferation may allow the design of individualised radiotherapy schedules to optimise response. This prospective study correlates the tumour proliferation rate of cervical carcinoma with response to conventional radiotherapy. The potential tumour cell doubling rate (Tpot) was estimated following flash labelling of the tumours in vivo using the DNA precursor, bromodeoxyuridine (BrdUrd); samples were analysed by flow cytometry. Tumour ploidy, DNA index and mitotic count were also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…For the patients treated with conventional fractionation (CF), the local control probability of the tumours with the LI of ≥ 52% were significantly higher than those with the LI of Ͻ 52% (P Ͻ 0.05). No significant difference was observed according to the PCNA LI for patients treated with AHF Bolger et al, 1996). In a preliminary analysis of the results of the EORTC trial (Begg et al, 1990), patients with short Tpot tumours had poor local control if given CF.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients treated with conventional fractionation (CF), the local control probability of the tumours with the LI of ≥ 52% were significantly higher than those with the LI of Ͻ 52% (P Ͻ 0.05). No significant difference was observed according to the PCNA LI for patients treated with AHF Bolger et al, 1996). In a preliminary analysis of the results of the EORTC trial (Begg et al, 1990), patients with short Tpot tumours had poor local control if given CF.…”
Section: Discussionmentioning
confidence: 99%
“…3 In other studies, expression of proteins: c-erbB-2, Ki-67, and the mitotic index of proliferating cell population are also demonstrated as predictor of tumor response. 9,10 Magnetic resonance imaging is also shown to distinguish tumors of low grade and high grade responsiveness to radiation therapy in carcinoma of uterine cervix. Further, monitoring the radiation response by both magnetic resonance imaging and NMR spectroscopy is also reported in literature.…”
Section: Introductionmentioning
confidence: 98%
“…The authors offer various potential explanations for the observation that more protracted or less dose intense chemotherapy was detrimental for survival and recurrence, and shorter cycle length and/or higher dose intensity neoadjuvant chemotherapy might be advantageous. They suggested that in these rapidly proliferating tumours [35], with a relatively high growth fraction [36], long cycle and/or low dose-intensity chemotherapy may not be effective in reducing repopulation with radiotherapy resistant cells. Alternatively, if prolongation of the duration of radiotherapy reduces local control by allowing extra time for repopulation with resistant cells [37] and there is chemotherapy and radiotherapy crossresistance, the duration of chemotherapy, delay to radiotherapy and duration of radiotherapy, could each have an impact on prognosis.…”
Section: Neoadjuvant Chemotherapy Prior To Radical Radiotherapy Versumentioning
confidence: 99%